2023
DOI: 10.1186/s40798-023-00552-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary, Functional, Cognitive and Mental Health Outcomes Post-COVID-19, Across the Range of Severity of Acute Illness, in a Physically Active, Working-Age Population

Abstract: Background The COVID-19 pandemic has led to significant morbidity and mortality, with the former impacting and limiting individuals requiring high physical fitness, including sportspeople and emergency services. Methods Observational cohort study of 4 groups: hospitalised, community illness with on-going symptoms (community-symptomatic), community illness now recovered (community-recovered) and comparison. A total of 113 participants (aged 39 ± 9, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
9
0
1
Order By: Relevance
“…Another study encompassing 547 patients evaluated through an online questionnaire nearly 300 days after the SARS-CoV-2 infection showed that >80% of people still reported lower quality of life, that was associated with pain, discomfort, or impairment of usual activities, and that was significantly more prevalent than in normative population [32]. Decreased quality of life compared to general population was also revealed among UK patients after 5 months since initial hospitalization due to COVID-19 and, interestingly, these individuals expressed higher fatigue rates with no significant accompanying differences during cognitive testing [33]. Finally, in authors' previous study related to non-hospitalized patients with COVID-19, some specific symptoms of brain fog were found to be associated with QoL-W impairment after 3 months since the onset of the SARS-CoV-2 infection [15].…”
Section: Discussionmentioning
confidence: 90%
“…Another study encompassing 547 patients evaluated through an online questionnaire nearly 300 days after the SARS-CoV-2 infection showed that >80% of people still reported lower quality of life, that was associated with pain, discomfort, or impairment of usual activities, and that was significantly more prevalent than in normative population [32]. Decreased quality of life compared to general population was also revealed among UK patients after 5 months since initial hospitalization due to COVID-19 and, interestingly, these individuals expressed higher fatigue rates with no significant accompanying differences during cognitive testing [33]. Finally, in authors' previous study related to non-hospitalized patients with COVID-19, some specific symptoms of brain fog were found to be associated with QoL-W impairment after 3 months since the onset of the SARS-CoV-2 infection [15].…”
Section: Discussionmentioning
confidence: 90%
“… Quality of life in covid-19 cases versus controls of studies reporting EQ-5D. 32–36 Symptomatic and asymptomatic groups of Pell and colleagues 36 were merged for the analysis. A negative mean difference value indicates lower quality of life in the covid-19 group.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time in this population, this study has been able to offer some limited predictive value in the development of post-COVID-19 symptomology. The value of these predictions will be explored further during the longitudinal M-COVID cohort study (1061/MODREC/20) 30…”
Section: Discussionmentioning
confidence: 99%